APLIKASI KOMPOS JERAMI PADI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L.) - Lisda Lisyah; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study is to get the best of rice straw compost and NPK fertilizer on the growth and production of peanuts. This research was conducted at the Faculty of agriculture experiment station, Riau University, Pekanbaru,  over four months from February - June 2016. This study used a completely randomized design factorial consisting of two factors and three replications. The first factor was the rice straw compost (P) consists of four levels: P0 =without rice straw compost, P1 = 7 tons/ha; P2 = 14 tons/ha, and P3 = 21 tons/ha. The second factor was the NPK fertilizer (N), which consists of four levels, namely N0 = withoutNPK fertilizer, N1 = 100 kg/ha, N2 = 200 kg/ha and N3 = 300 kg/ha. The parameter observed were plant height, number of effective nodules, the weight of effective nodules, the amount of flowers, the number of primary branches, number of pithy pods per plant, number of seeds per plant, seed weight per plant, grain weight per m2, weight of 100 seeds. Data obtained were analyzed by analysis of variance and Duncan's Multiple Range Test at 5%. Provision of rice straw composts 21 tons/ ha and 200 kg NPK /ha and 300 kg/ha is the best dosing and gave peanut production 141,16 g/m2  (1,41 tons/ha) and 147,48 g/m2                       (1,47 tons/ha).  Key words:Arachis hypogaea L., rice straw compost, fertilizer NPK